Evaluation of Air Flow in a Computer Casing using Computational Fluid Dynamics. - Pardamean, Reynold
Overheated electronic component can lead to degradation of system performance and system damage. A good air circulation inside a computer is casing is needed to prevent overheated components. The efectiveness of air circulation inside a computer case can be evaluated through Computational Fluid Dynamics (CFD) simulation This final project deals with an example of CFD application for simulating air circulation inside computer casing of a computer sever in Thermodynamics Laboratory. The geometry model development and the simulation calculation were done using GAMBIT 2.4.6 and 6.3.26 sortwares, respectively. The simulation shows that the air circulation and the heat transfer inside the computer casing are good. Even so, several modifications were done by adding a passive component and relocating a computer’s component. The simulation result shows that the modification can improve air circulation is certain areas. The simulated air temperature were validate by comparing them to their associating measured values. The temperature validation shows that the simulationn could well represent the actual air circulation. Further research of this topic can be done by considering heat dissipation on each computer component inside the computer casing, so that the simulation accuracy could be improved.